2004
DOI: 10.1097/00000542-200402000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Decreases Perioperative Tissue Oxygenation

Abstract: Wound and tissue hypoxia were common in obese patients in the perioperative period and most pronounced during surgery. Even with supplemental oxygen tissue, oxygen tension in obese patients was reduced to levels that are associated with a substantial increase in infection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
236
5
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(264 citation statements)
references
References 26 publications
12
236
5
9
Order By: Relevance
“…Adipocyte hypertrophy creates areas of local AT microhypoxia at the earliest stages of expansion (19). This has been verified by recent clinical observations in humans, which suggest that AT is poorly oxygenated in the obese state (20,21). The effects of the local AT hypoxia have been investigated both in isolated murine adipocytes and in animal models (4,(22)(23)(24)(25).…”
Section: Macrophages Major Constituents Of At and Mediators Of Remodmentioning
confidence: 74%
See 1 more Smart Citation
“…Adipocyte hypertrophy creates areas of local AT microhypoxia at the earliest stages of expansion (19). This has been verified by recent clinical observations in humans, which suggest that AT is poorly oxygenated in the obese state (20,21). The effects of the local AT hypoxia have been investigated both in isolated murine adipocytes and in animal models (4,(22)(23)(24)(25).…”
Section: Macrophages Major Constituents Of At and Mediators Of Remodmentioning
confidence: 74%
“…We have discussed hypoxia as a key player in expanding AT that serves as a driving force for macrophage infiltration. Compared to brown AT, white AT is not particularly well vascularized (4,20). The O 2 tension in obese white AT can reach levels as low as 15 mmHg, much lower than that in normal lean AT, in which values would typically reach 45-50 mmHg (23).…”
Section: Angiogenesis a Rate-limiting Step For At Expansion And Remomentioning
confidence: 94%
“…SSI is the most common complication after colectomy, and obesity or overweight is thought to increase this risk by 2.5-to 5-fold as compared with patients of normal weight [13][14][15][16]. This risk may be related to the decreased oxygen tension in relatively avascular adipose tissue, differences in wound healing, greater wound size, or technical difficulties [13,17]. However, another report suggests that obesity or overweight is not a risk factor for SSI after colectomy [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that obese subjects often present a low-degree chronic inflammation within the adipose tissue [27,33]. Furthermore, it has been reported that this tissue is under chronic hypoxic conditions during the development of obesity [22,48], although a situation of decreased adipose tissue oxygen tension in obese compared to lean men may not always occur [18], which would be explained by a lower adipose tissue oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%